Psychosocial determinants of recidivism risk among incarcerated individuals with a history of substance use: A systematic review - Kalaivanan Syasyila; Mohammad Rahim Kamaluddin; Hilwa Abdullah @ Mohd Nor; Paramjit Singh Jamir Singh (PLoS ONE, 2025)
The prevalence of recidivism among individuals with a history of substance use and incarceration remains a significant concern for criminal justice systems worldwide. With significant social and economic ramifications, preventing people with a history of substance use from reoffending is a substantial issue. It is imperative to comprehend the complex connections between psychological and social factors to continue developing successful therapies. To better understand this complexity, this review provides a comprehensive analysis of how psychological vulnerabilities and social barriers combine to influence reoffending. Our search strategies in major databases, including Scopus, Web of Science (WoS), ScienceDirect, PubMed, and PubMed Central (PMC), yielded 34,766 results, which decreased to 858 articles after eliminating ineligible records, duplicates, and records unrelated to the language. Finally, 30 articles qualified to be included in the systematic review following PRISMA guidelines. In addition to social determinants, including family support, community impact, stigma, and peer influence, the review concentrated on psychological issues like drug abuse, dual diagnoses, and early-life adversity. The review highlights the importance of social support, with strong family and community relationships associated with reduced recidivism risk. Mental health issues, particularly those co-occurring with substance use, impede reintegration, with emotional dysregulation and poor decision-making contributing to continued criminal conduct. Other significant risk factors include involvement in a gang, trauma exposure, and a lack of rehabilitative assistance. The results highlight that recidivism is a fundamentally psychological and societal problem rather than just an individual one. Breaking reoffending cycles requires addressing these elements through comprehensive, long-term interventions. Given possible gender disparities in recidivism pathways, future systematic reviews should consider doing separate syntheses for men and women to provide more focused insights.